Teaching of Islamic Studies at the Junior and Senior Secondary Levels within the 6-3-3-4 Educational Structure - Opeloye, M. O. (2014)
The 6-3-3-4 structure is a recently adopted system which allows students to spend 6 years in the primary school, 3 years in the junior secondary school. Another 3 years in the senior secondary school and finally 4 years in the University. The 6-5-2-3 which was abolished allowed students to spend 6 years in the primary school, 5 years in the secondary school, 2 years in higher secondary school and 3 years in the university.